2004
DOI: 10.17487/rfc3740
|View full text |Cite
|
Sign up to set email alerts
|

The Multicast Group Security Architecture

Abstract: This document provides an overview and rationale of the multicast security architecture used to secure data packets of large multicast groups. The document begins by introducing a Multicast Security Reference Framework, and proceeds to identify the security services that may be part of a secure multicast solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 6 publications
0
95
0
Order By: Relevance
“…At the time this document was published, the MSEC working group was actively working on standardizing protocols to provide multicast security [17]. Multicast-based solutions relying on IPsec should specify how to meet the security requirements in [4].…”
Section: Using Ipsec With Forcesmentioning
confidence: 99%
“…At the time this document was published, the MSEC working group was actively working on standardizing protocols to provide multicast security [17]. Multicast-based solutions relying on IPsec should specify how to meet the security requirements in [4].…”
Section: Using Ipsec With Forcesmentioning
confidence: 99%
“…Multicast security is as important as unicast security whereas multicast security is more complicated than unicast security, e.g. [22], [23]. The authors are studying to extend the proposed model for supporting multicast security [24], where a device can pay the small penalty of processing overhead and memory.…”
Section: Further Study Itemsmentioning
confidence: 99%
“…Hardjono, 1999, Canetti et al, 1999, Moyer et al, 1999. In particular, Abdalla et al (2000) suggested a key management scheme which occasionally tolerates a controlled number of free-riders.…”
Section: Related Workmentioning
confidence: 99%